Education in the colonies of the Jewish Colonization Association in Argentina - Edgardo Enrique Zablotsky (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2016)
The philanthropic activity of Baron de Hirsch was clearly marked by one characteristic: not providing charity but attempting the economic rehabilitation of the beneficiaries. Hirsch systematically suggests that education and professional training were the only way to break the vicious circle of poverty. For instance, for more than a decade Baron de Hirsch spent his time and money in the economic rehabilitation of his coreligionists, both in the Ottoman Empire and in the Austro-Hungarian Empire, through education and professional training. In 1891, after discarding the possibility of improving the quality of life of Jews in the Russian Empire through the establishment of an educational system, similar to what was done in other societies, Hirsch founded the Jewish Colonization Association (J.C.A.) through which he would manage the immigration of thousands of people to Argentina and their settlement in agricultural colonies. The original rules of the J.C.A. gave Hirsch full control over the activities of the Association; therefore, this paper hypothesized that the educational actions of the Jewish Colonization Association in the colonies should have been all consistent with Hirsch's vision on education. The evidence presented clearly supports this hypothesis.
Keywords: D64; 330; Barón Maurice de Hirsch; Jewish Colonization Association; education